(untitled) - Huchzermeyer, Richard Lynn

Measuring mechanical properties using digital image correlation: extracting tensile and fracture properties from a single sample. (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.